Eksplorasi Relativistik Fenomena Dilatasi Waktu: Studi Kritis Perjalanan Roket melalui Simulasi Virtual Walter Fendt - Septi Maria; Jessica Urischiliya Banjarnahor; Katherine Cindy Apriliana Sibarani; Cesilia Sondang Uli Sitanggang; Vesona Cahya Rohana Sinaga; Dame Lamtiur Simanjuntak; Veronika Vransiska Tarigan; Cinta Marcella Namira; Ribka Nainggolan; Arya Sandro Simanjorang (Lembaga Bale Literasi, 2026)
This study aims to explore the phenomenon of time dilation based on the Special Theory of Relativity through the Walter Fendt Relativity Simulation. The main problem in this research is how the relative velocity of an object affects the difference in time rates between two observers in different reference frames. The research employs a virtual experimental method with a descriptive quantitative approach. Data were obtained from simulations with relative velocities of (v/c = 0.3, 0.6, 0.8, 0.9, and 0.95), which were then compared with theoretical calculations using Einstein’s time dilation equation. The results indicate that as the relative velocity increases, the time difference between the two observers becomes greater. The percentage of agreement between the simulation and theoretical results shows a very small deviation, indicating that the Walter Fendt simulation has good validity in representing the concept of time dilation. These findings suggest that virtual simulations are effective in enhancing the understanding of relativistic concepts in modern physics learning.